Estimating Milkweed Abundance in Metropolitan Areas Under Existing and User-Defined Scenarios - Johnston, Mark K.; Hasle, Aster F.; Klinger, Karen R.; Lambruschi, Marc P.; Derby Lewis, Abigail; Stotz, Douglas F.; Winter, Alexis M.; Bouman, Mark J.; Redlinski, Izabella (Frontiers in Ecology and Evolution, 2019)
Metropolitan areas play an undetermined role in supporting migratory monarch butterfly (Danaus plexippus) populations by providing habitat areas rich with milkweed (Asclepias spp.), the obligate host plants for monarch larvae. Researchers from the US Geological Survey and collaborating institutions have called for an “all hands on deck” approach to establishing monarch butterfly habitat by focusing on potential contributions from all land use sectors at levels necessary to sustain the eastern migratory monarch butterfly population. Our research teams surveyed milkweed densities across four major metropolitan areas (Chicago, Minneapolis-St. Paul, Kansas City, and Austin) using a new “metro-transect” protocol. We developed Geographic Information System (GIS) tools that use these data to model the baseline, or existing, milkweed stems present in metropolitan areas, and to estimate the potential to add additional milkweed stems with the adoption of milkweed-friendly planting practices across different land use classes (e.g., residential, institutional, commercial). By extrapolating metropolitan Chicago milkweed densities across US Census urbanized areas in the entire eastern range of monarch butterflies, we estimate that approximately 36 million stems of milkweed can be added under modest “enhanced” milkweed densities, and up to 795 million stems may be added under “exemplary” milkweed densities. Both estimates are derived from a two percent “adoption rate,” or landowner conversion of green spaces, based on field observations. These findings show that metropolitan areas provide important habitat opportunities and should be included prominently in Midwestern monarch conservation strategies when working toward national goals to increase the amount of milkweed stems and monarch habitat across the Midwest. Municipal decision-makers and planners can estimate their capacity to add stems across the metropolitan landscape by identifying where the biggest opportunities exist with help from our Urban Monarch Conservation Planning Tools.